Assessing antimicrobial consumption in public and private sectors within the Costa Rican health system: current status and future directions - José Pablo Díaz-Madriz; Carolina Rojas-Chinchilla; Esteban Zavaleta-Monestel; Shing Mi Ching-Fung; Hugo Marin-Piva; Gustavo H Marin; Lucia Giangreco (BMC, 2024)
Abstract Background Antimicrobial resistance is a significant global health threat. Therefore, robust surveillance systems for antimicrobial consumption (AMC) are essential to develop public health strategies. However, Latin American countries, including Costa Rica, face challenges in regularly reporting AMC data. This study aims to estimate and analyse the overall AMC in Costa Rica for 2019. Methods This study is a national-level, retrospective, observational, and descriptive analysis of AMC in Costa Rica from 1 January to 31 December 2019. The study followed the World Health Organization (WHO) guidelines for the Surveillance of National AMC. The Anatomical Therapeutic Chemical (ATC) / Defined Daily Doses (DDD) system was used to analyse types of antimicrobials and DDD per 1000 inhabitants per day (DID). Antimicrobial dispensation data from the Costa Rican Social Security Fund (CCSS) represented the public sector, while the private sector data was sourced from IQVIA. The analysis included data from both inpatient and outpatient sectors. Results A total AMC of 14.32 DID, of which 12.75 DID was within the public sector and 4.12 DID was within the private sector. Penicillins had the highest consumption nationally and in the public sector, while macrolides and lincosamides predominate in the private sector. According to the WHO-AWaRe (Access-Watch-Reserve) classification, antibiotics predominantly consumed nationally (74.7%) and in the public (83.0%) sectors are categorized under Access, whereas the private (61.0%) sector predominates the Watch category. Conclusion This study illustrates the importance of enhancing AMC surveillance by integrating data from both the public and private sectors. The findings indicate an excessive use of "Watch" antimicrobials in the private sector. To address this issue, all sectors and regulatory authorities must play an active and supportive role, in the development of effective, multisectoral policies. The methodology employed in this study is applicable to other Latin American countries, and therefore should be utilized for future analysis AMC in this region.